Association of Depression with Internet Addiction among Students of a Public University in Bangladesh (International Journal of Statistical Sciences, 2026)
Depression is a common mental health problem among university students and can get worse due to Internet Addiction (IA). This study aimed to examine how common depression is and how it is linked to IA among students at Rajshahi University in Bangladesh. This cross-sectional study surveyed 1,014 second- and third-year undergraduate students at Rajshahi University using a multistage sampling method. Data were collected using a structured questionnaire that included the Patient Health Questionnaire- 9 items (PHQ-9) to measure depression and Young's Internet Addiction Test (IAT) to assess IA. The collected data were analyzed using the Chi-square test and a multiple logistic regression model. The respondents had a mean age of 22.18 years; most were male (67.1%), from nuclear families (81.1%), and lived in rural areas (65.0%). Most students (59.8%) were addicted to the internet, and nearly half (48.2%) showed signs of depression. Among those addicted to the internet, 72.8% also experienced depression. IA was found to be significantly associated with depression (aOR: 4.73, 95% CI: 3.48-6.44). Students in the Commerce faculty were identified as more likely to be depressed compared to those in the Arts faculty (aOR: 1.41, 95% CI: 1.01-1.96). Being underweight (aOR: 1.62, 95% CI: 1.08-2.42) and engaging in nocturnal internet use (aOR: 1.86, 95% CI: 1.16-2.99) were also significantly associated with depression. This study found a high prevalence of IA and depression among university students, with a strong link between the two. Students addicted to the internet were significantly more likely to experience depression. Depressive symptoms were also more common among Commerce faculty students, underweight individuals, and those using the internet at night. These findings highlight the need for targeted mental health support, awareness initiatives, and strategies to promote responsible internet use among university students.IJSS, Vol. 26(1), March, 2026, pp 13-23